Preconditioning With Intermittent Hypobaric Hypoxia Attenuates Stroke Damage and Modulates Endocytosis in Residual Neurons - Wan, Yaqi; Huang, Lu; Liu, Yanmin; Ji, Weizhong; Li, Changxing; Ge, Ri-li (Frontiers in Neurology, 2021)
Background: Moderate hypobaric hypoxia induces cerebral ischemic tolerance. We investigated the optimal method for applying hypobaric hypoxia preconditioning at 5000 m to ischemic brain tissue and combined it with proteomics to determine the mechanisms underlying this effect. Methods: Male SD rats were randomly grouped as S (sham, n=20), M (middle cerebral artery occlusion [MCAO], n=28), H2M (intermittent hypobaric hypoxia preconditioned MCAO group, 2 h/day, 10 days, n=20), H6M (intermittent hypobaric hypoxia preconditioned MCAO group, 6 h/day, 10 days, n=28), and HpM (persistent hypobaric hypoxia preconditioned MCAO group, 10 days, n=28). The permanent MCAO model was established based on the Zea Longa method. Infarction was assessed with the modified neurological severity score (mNSS) and 2,3,5-triphenyl tetrazolium chloride staining. The total protein expression of the neuron-specific nuclear protein (NeuN), cysteinyl aspartate specific proteinase 3 (caspase-3), cleaved-caspase-3, and interleukin 6 (IL-6) was determined using western blotting. We assessed the peri-infarct cortex’s ultrastructural changes. A label-free proteomic study and western blot verification were performed on the most effective preconditioned group. Results: The H6M group showed a lower infarct volume (p=0.0005), lower mNSS score (p=0.0009) than the M group. The H2M showed a lower level of IL-6 (p=0.0213) than the M group. The caspase-3 level decreased in the H2M (p=0.0002), H6M (p=0.0025), and HpM groups (p=0.0054) compared with that in the M group. Cleaved-caspase-3 expression decreased in the H2M (p=0.0011), H6M (p<0.0001), and HpM groups (p<0.0001) compared with that in the M group. The neurons’ ultrastructure and the blood-brain barrier in the peri-infarct tissue improved in the H2M and H6M groups. Immunofluorescence revealed increased NeuN-positive cells in the peri-infarct tissue in the H6M group (p=0.0003, H6M vs. M). Protein expression of Chmp1a, Arpc5, and Hspa2 factors related to endocytosis were upregulated in the H6M compared with those of the M group (p<0.05 for all) on western blot verification of label-free proteomics. Conclusions: Intermittent hypobaric hypoxia preconditioning exerts a neuroprotective effect in a rat stroke model. Persistent hypobaric hypoxia stimulation exhibited no significant neuroprotective effect. Intermittent hypoxic preconditioning for 6 h/day for 10 days upregulates key proteins in clathrin-dependent endocytosis of neurons in the cortex.